A rare case of vein of galen thrombosis: exploring a potential role for novel oral anticoagulants (NOACs) in cerebral deep vein thrombosis - Inche Mat, Liyana Najwa; Wan Sulaiman, Wan Aliaa; Hoo, Fan Kee; Mohammad Sallehuddin, Hakimah; Basri, Hamidon (Pakistan Medical Association Rawalpindi Islamabad Branch, 2017)
Cerebral deep vein thrombosis is rare but it carries high morbidity and mortality. The mainstay of treatment is anticoagulation with vitamin K antagonist (VKA). However, VKA has a lot of drawback of fatal bleeding in Asian population, drug-drug and drug-food interactions and the need for frequent INR monitoring when compared to novel oral anticoagulants (NOACs). Here, we present a case of a 52-year-old lady who was admitted with 3 days history of a headache and confusion. Physical examinations revealed no long tract signs and blood investigations were normal. Thrombosis of the vein of Galen was diagnosed on MRI of the brain. We describe successful treatment with subcutaneous low molecular weight heparin for 2 weeks followed by oral direct thrombin inhibitor dabigatran.